Tehnika in tehnologija v prepletenosti z drugimi področji - Cencelj, Zvonka (Revija za elementarno izobraževanje, 2010)
Technology and crafts in connection to other fields. This article presents aspects of project learning, collaborative learning and research learning in the subject of technology. Project learning can provide a learning process that gives pupils and teachers a more creative and relaxing atmosphere. This is an element that is lacking in our primary schools at the moment. Children can develop themselves more universally when they use their mind, body, emotions and soul.